PERAN KOMPETENSI PEDAGOGIK DAN PROFESIONAL TERHADAP KENERJA GURU EKONOMI: (The Role of Pedagogic and Professional Competency on The Performance of Economics Teachers) - Supriyanto Supriyanto (Perspektif Pendidikan dan Keguruan, 2019)
This study aims at determining whether pedagogic competence and professional competence influence the performance of Economics teachers. For this purpose, a population of 23 teachers and 600 students was established, from which 23 teachers and 234 students were sampled. Data collection was by questionnaire for the pedagogical competence variable, while for professional competency variables and teacher performance was by observations made by researchers when the teachers were teaching. Data was analyzed using multiple linear regression analysis techniques. The results of the study show that pedagogic competency and professional competence simultaneously have a significant effect on the performance of Economics teachers, because the analysis indicated that Fcount > Ftable. This can be seen from the figures of the Fcount which is equal to 31.404, while Ftable for dfn-k-1 = 20 (sig = 0.05) which is 3.493. Since R = 0.871 and R2 = 0.758 at p < 0.01, the indication is that the effect of pedagogic competence and professional competence on the performance of Economics teachers is very strong, because it is able to predict 75.8%, while 24.2% is predicted by other variables outside of the scope of this research. Partially, the results of a simple correlation analysis between pedagogical competencies and performance of Economics teachers show that r = 0.815 at p < 0.01, indicating that pedagogic competence has a significant effect on the performance of Economics teachers. Likewise, professional competence and performance of Economics teachers show that r = 0.800 at p < 0.01, meaning that professional competence has a significant effect on teacher performance